2017
DOI: 10.1186/s13568-017-0385-2
|View full text |Cite
|
Sign up to set email alerts
|

Ammonia production from amino acid-based biomass-like sources by engineered Escherichia coli

Abstract: The demand for ammonia is expected to increase in the future because of its importance in agriculture, industry, and hydrogen transportation. Although the Haber–Bosch process is known as an effective way to produce ammonia, the process is energy-intensive. Thus, an environmentally friendly ammonia production process is desired. In this study, we aimed to produce ammonia from amino acids and amino acid-based biomass-like resources by modifying the metabolism of Escherichia coli. By engineering metabolic flux to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 22 publications
(22 reference statements)
1
25
0
Order By: Relevance
“…In this study, we displayed glutaminase, YbaS, on the yeast cell surface to produce ammonia from glutamine included in pretreated soybean residues outside the cells. Figure 3 shows that YbaSdisplaying yeast produced 3.34 g/L ammonia, which was 1.4 times and 7.3 times higher than the ammonia concentration in the previous studies by metabolically engineered B. subtilis and E. coli (Choi et al 2014;Mikami et al 2017). Therefore, we succeeded in producing highconcentration ammonia using yeast for the first time.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…In this study, we displayed glutaminase, YbaS, on the yeast cell surface to produce ammonia from glutamine included in pretreated soybean residues outside the cells. Figure 3 shows that YbaSdisplaying yeast produced 3.34 g/L ammonia, which was 1.4 times and 7.3 times higher than the ammonia concentration in the previous studies by metabolically engineered B. subtilis and E. coli (Choi et al 2014;Mikami et al 2017). Therefore, we succeeded in producing highconcentration ammonia using yeast for the first time.…”
Section: Discussionmentioning
confidence: 75%
“…However, there are few reports of successful biological technologies for the sustainable utilization of nitrogen (Vong et al 2016). Some bacteria producing ammonia from biomass were previously created with metabolic engineering (Choi et al 2014;Mikami et al 2017). Disruption of the genes related to assimilation and overexpression of the genes catabolizing amino acids were effective for producing ammonia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A driving force for deamination would allow more carbon skeletons to be released from amino acids for product formation, and the strategies for creating the driving force have been well demonstrated in E. coli by Huo et al (Huo et al, 2011). It was shown that deamination could be facilitated by deletion of genes related to ammonium-assimilation pathway (Huo et al, 2011; Mikami et al, 2017). Furthermore, introduction of exogenous transamination-deamination cycles further drained amino acids that serve as nitrogen reservoir as the result of transamination…”
Section: Resultsmentioning
confidence: 99%
“…Recently, the same idea has been applied for production of biofuels from DDGS by a bacterial consortium which consists of two strains designed for selective utilization of carbohydrates and amino acids, respectively [ 115 ]. The strategy by deamination of amino acids has also been exploited for the production of ammonia [ 116 ].
Fig.
…”
Section: Bio-based Production Of Fuels and Chemicals From Amino Acidsmentioning
confidence: 99%